Innovating Traditional Production Systems Through On-Farm Conservation Agriculture and Agroforestry Research - Fonteyne, Simon; Silva Avendaño, Columba; Ramos Sanchez, Angel; Torres Zambrano, Juan Pablo; García Dávila, Fernando; Pérez Martínez, Zenaida; García Dávila, Alejandrina; Castillo Villaseñor, Luis; Verhulst, Nele (Frontiers in Agronomy, 2022)
Maize (Zea mays L.) the staple crop of Mexico, is often produced by smallholder farmers on sloping terrains. Historically, little agronomic research has been performed under the conditions of these farmers to support them in the sustainable intensification of their production systems. We set up trials at two locations in the state of Oaxaca to evaluate conservation agriculture and agroforestry in collaboration with local farmers. Crop diversification through crop rotations, multicropping, relay cropping or agroforestry increased system yields the most, while increased input use through increased fertilization or liming did not increase profitability enough to justify their use. Zero tillage and residue retention increased yields and reduced production costs. Conservation agriculture with agroforestry was a high-yielding, profitable system that also reduced farmers’ risk by providing several harvests per year. In several years the main crop failed, while the trees were able to produce due to their different growing season compared to maize. Through adaptive investigation under farmers’ conditions, sustainable intensification of traditional production system is possible with low-cost changes that are locally adapted and within farmers’ possibilities.